Mechanism For Resolving Criminal Cases After A Bankruptcy Decision - Adli, Muhammad (Inspiring Law Journal, 2024)
Problems then arise when, before or after the bankruptcy declaration decision is pronounced, it turns out that the bankrupt debtor's bankrupt assets which are included in the Curator's inventory list have been confiscated by investigators in connection with alleged criminal acts committed by the bankrupt debtor, where the confiscation action carried out by the investigator is based on Article 39 Paragraph (2) of the Criminal Procedure Code which must be in accordance with the provisions of Article 39 Paragraph (1) of the Criminal Procedure Code. The provisions on general confiscation are in conflict with criminal confiscation, because Article 31 of the Bankruptcy and PKPU Laws gives priority to general bankruptcy confiscation, whereas criminal confiscation is regulated in Article 39 paragraph (2) of the Criminal Procedure Code, which also gives priority to criminal confiscation. This conflict is further strengthened by the dichotomy between public law and private law, thus giving rise to legal uncertainty and hindering the curator in carrying out his duties to settle the bankrupt's assets, which automatically harms the creditors as victims